The immigrant wage gap in Canada: Quebec and the rest of Canada - Nadeau, S.; Seckin, A. (My University, 2010)
This paper examines the nature of the differences in the wage gap between Canadian born males and immigrant males in Quebec and in the rest of Canada (ROC) over the period 1980-2000. Relative to Canadian born individuals, immigrants in the ROC have been consistently, and increasingly, faring better in terms of wages than immigrants in Quebec. We cannot conclude that this is a consequence of Quebec having different immigration policies than the ROC, as the wage gap would be even larger if Quebec attracted the same immigrants as the ROC, nor can we conclude that immigrants are more discriminated against in Quebec. We find that the increased differential in the Quebec-ROC immigrant wage gap mostly reflects changes in the premium earned by immigrants who become citizens over those who remain landed immigrants; this premium virtually disappeared in Quebec while remaining stable in the ROC over the period.
Keywords: Immigrants Vs Canadian Born İndividuals; Immigration Policies; Quebec And The Rest Of Canada; Wage Differentials; İmmigrant; İmmigration Policy; Racism; Wage Gap; Canada; Quebec [Canada]